Evsizler ve toplum sağlığı - (:unkn) unknown (My University, 2010)
Evsizlik, tüm dünya ülkelerinde önemli toplum sağlığı sorunlarından biridir. Son yıllarda ekonomik, sosyal ve politik faktörlerin etkisiyle, evsiz kadın, erkek ve çocukların sayısı önemli ölçüde artmıştır. Evsizlik, sağlık risklerine ve problemlerine sebep olmaktadır. Evsiz erkek, kadın ve çocuklar, evi olanlara göre daha fazla sağlık problemleri yaşamakta ve sağlık bakımı almada birçok engelle karşılaşmaktadırlar. Bu makalede, toplum içinde önemli bir risk grubu olan evsiz insanlar, sağlık riskleri, evsizlere yönelik toplum sağlığı hizmetleri ve sağlığı koruma düzeyleri doğrultusunda toplum sağlığı hemşiresinin sorumlulukları tartışılmaktadır.

Homelessness is one of the important public health problems in world countries today. The number of homeless men, women and children has been increased in alarming rate with economic, social and political factors in recent years. Homelessness causes health risks and problems. Homeless men, women and children experience more health problems than people who live in home and often encounter multiple barriers when they attempt to obtain health care. Homeless people who are one of the major risky populations in community, their health risks, community health services for homeless people and responsibilities of community health nurses in terms of health prevention levels are discussed in this article.
Homeless people and community health
Keywords: Sağlık Bilimleri ve Hizmetleri; Temel Sağlık Hizmetleri; Sağlık Politikaları ve Hizmetleri; Sosyal Çalışma; Sosyoloji